The paradox of self-consciousness - Bermúdez, José Luis (Representation and mind., 1998)
In this book, Jose Luis Bermudez addresses two fundamental problems in the philosophy and psychology of self-consciousness: (1) Can we provide a noncircular account of full-fledged self-conscious thought and language in terms of more fundamental capacities? (2) Can we explain how full-fledged self-conscious thought and language can arise in the normal course of human development? Bermudez argues that a paradox (the paradox of self-consciousness) arises from the apparent strict interdependence between self-conscious thought and linguistic self-reference. Responding to the paradox, the author draws on recent work in empirical psychology and philosophy to cut the tie between self-conscious thought and linguistic self-reference.